Urban Greening for New Capital Cities. A Meta Review - de Vries, Walter Timo (Frontiers in Sustainable Cities, 2021)
In light of the discussions on relocating the capital city of Indonesia to a new location in Kalimantan, and create a new green capital city (referred to as IKN), the purpose of this meta-review paper is learn from experiences from other relocations of capital cities and creations of green cities in the world. Specific emphasis is hereby given to urban greening and gentrification. This article applies a meta-analytical approach by connecting the basic tenets of the 8R framework of responsible land management to assess the pros and cons of a selected set of capital city relocations and green cities. From the comparison, it is possible to generate general recommendations for Indonesia's new green capital city. The comparison reveals that each of the selected cases falls short in one or more aspects of the 8R framework. In all cases, constructing green capitals requires a mixed and integrated land use planning, a transparent regulatory framework toward land use control, extensive consultation with both local, national and international stakeholders, and participation with local residents. Only under these conditions, one can ensure ownership, respect and trust in the decision. The quandaries highlight the complexity of capital city relocation and green city creation. The originality lies in the specific land management framework perspective and discursive analysis of documented discourses on constructing new capital and green cities. This provides new options for devising and extending regulatory guidelines and for assigning responsibilities for such new mega-endeavors. Given the conceptual and discursive character of the paper, a limitation of the approach may be that there are no specific empirical data collected, yet several recommendations for further research include expanding the boundary work between the land management, the spatial planning and governance domains.